Enhancing Teacher Attendance Discipline through the Implementation of Reward and Punishment Systems in Elementary Schools - Nurhidayah, Nunung (Journal of Social Studies Arts and Humanities (JSSAH), 2024)
Teacher discipline plays a pivotal role in maintaining instructional quality and professional integrity within educational institutions. This study aims to analyze the effectiveness of applying reward and punishment systems in improving teachers’ attendance discipline during classroom teaching activities at SD Negeri Cibalagung 2, Bogor City. The research utilized a School Action Research (SAR) design, conducted in two cycles involving ten elementary teachers. Data were collected through observation sheets, attendance records, and documentation, then analyzed descriptively to assess behavioral improvement. The findings revealed a significant increase in teacher punctuality and classroom presence, with the rate of delayed attendance (15 minutes) decreasing from 47.83% in the first cycle to 0% in the second. The implementation of clear incentives and corrective sanctions not only enhanced compliance but also fostered accountability and motivation among teachers. These results suggest that a well-structured reward and punishment mechanism can effectively strengthen organizational discipline, improve teaching consistency, and support the creation of a positive school culture oriented toward quality education.